ANALISIS PENGENDALIAN KUALITAS PRODUK OIL SEAL PADA PT DINAMIKA ANUGERAH - Andra Fernando Siahaan; Sumantika, Arsyad (LPPM Universitas Putera Batam, 2023)
PT Dinamika Anugerah is a local company that produces oil seals and rubber molding for the needs of the automotive and non-automotive industries in Indonesia. The oil seal is a component on the engine part that functions to seal off the lubricant and prevent dirt and dust from entering the engine. The problem experienced by PT Dinamika Anugerah was the 33 NMB oilseal product which had a defective product exceeding the company's tolerance for defects, namely 0.5%. The number of Oil seal NMB products was 33 from September 2021 to August 2022, the percentage of defective products was 1.0290%. This research uses the method used is the Statistical Process Control (SPC) method to control quality control. As well as FTA to find loopholes to improve and minimize defective products and provide repair solutions with 5W + 1H and Based on the results of the analysis using Check Sheets it is known that the average defective caused by Spring 12 months material with a quantity of defective products is 1712 out of a total production of 166416 product is 1.0290%. When compared with the tolerance limit of the company's defective products (by 0.5%) this exceeds the tolerance limit so that the analysis of the causes of defective products and From the fishbone diagram above, it can be seen that defective Spring Pop out occurs due to several factors, namely coming from human/worker factors, production machines, working methods.